The Case of Toxic Leadership on Mars Hill: Conflict Framing and Image Restoration Strategy in the Devolution and Dissolution of a Megachurch - Spradley, R. Tyler; Spradley, Elizabeth (Journal of Leadership, Accountability and Ethics, 2020)
Large-scale, highly publicized organizational conflicts constitute organizational crises by threatening the normalcy and vitality of organizing. This study examines the case of toxic leadership within a megachurch, whose pastor and other leaders were over or founders of multiple organizations. Integrating 1) issue development within organizational conflict framing literature and 2) image restoration strategies within crisis communication literature, this study examines how issues were named, blamed, and claimed in public organizational texts during the outing of toxic leadership. Conclusions highlight the value of multiple and complimentary frameworks to analyze crisis communication and leadership.